NEGATIVE POLITENESS STRATEGIES IN BATAM COMPANIES' ENGLISH BUSINESS LETTER - Afriana Afriana; Ambalegin Ambalegin; Suhardianto Suhardianto (IdeBahasa, 2023)
This research aimed to the being pessimistic politeness strategy in the text of business letter from several Companies in Batam, Riau Island, Indonesia. This study includes multiple companies, with three companies chosen at random. Brown and Levinson (1987) define negative politeness methods as displaying restraint, formality, and distance. A descriptive qualitative method was used in analyzing the data because it would be explained by words, phrases, and sentences. The researcher employed the Sudaryanto (2015) observational method to obtain data. Brown and Levinson identified five negative politeness methods; however, in this study, the researchers focused solely on the pessimistic strategy. Pragmatics identity method was applied in analyzing the data. it was found that there were nine strategies of being pessimist politeness in the text of business letters. There are 2 data of being pessimistic in Letter 1 by PT. Vancouver Manufacturing Company, 4 data of being pessimistic in the Letter 2 by ABC Software Company, and 3 data of being pessimistic in Letter 3 by Mass Airlines Company.